Kemampuan Pemecahan Masalah Matematis Siswa pada Pembelajaran Problem Based Learning - Muhsin Hanis; Wahyudin Wahyudin; Fitriani Andhin Dyas (Mandalika Mathematics and Educations Journal, 2025)
This study aims to analyze and describe students’ mathematical problem-solving (MPS) ability through the implementation of PBL treatment on the topic of the perimeter of plane figures in fifth-grade elementary students. The research employed a quantitative approach with a pre-experimental design, specifically a one-shot case study. The participants consisted of 21 fifth-grade students selected using a purposive sampling technique. The research instrument was a problem-solving test that had been validated for both validity and reliability. The results indicate that PBL contributes significantly to students’ achievement in problem-solving ability. Based on the one-sample t-test, the significance value obtained was < 0.001, indicating that the proposed hypothesis was accepted at the 0.05 significance level. Furthermore, the students’ mean MPS score was 85.39, with a median of 90 and a skewness value of -1.320, which signifies a left-skewed distribution, meaning that most students achieved high scores. Furthermore, when viewed across the four problem-solving procedures, only the third stage—solving problems according to the determined procedures—had a percentage below 70%. This lower percentage was primarily due to inaccuracies in calculation processes, which affected the final results. Such errors were more likely caused by miscalculations rather than by the selection of inappropriate problem-solving strategies.